Improvement of key exchange cryptosystem using matrix with three-pass protocol / Annuur Zakiah Zainol, Farah Deena Mohamad Fisal, Fatin Nur Athirah Mohd Radzi - Zainol, Annuur Zakiah; Mohamad Fisal, Farah Deena; Mohd Radzi, Fatin Nur Athirah (2018)
These days, people need a more secure ways to share important message secretly. Public-key exchange cryptographic and encryption technique in Hill Cipher are one of the secured ways that people can use to share their message. No matter how hard to break the system, advisory always find a way to dismantle the message. Therefore, cryptosystem needs improvement from time to time. In the previous work of the research paper by Kester (2012), there are only one encryption process in public-key exchange. In this study, we concerning to increase the number of encryption in order to be difficult to break. In three-pass protocol, parties uses private encryption key to generate a cipher text. However, advisory can easily attack and obtain the private encryption key. Whereas, the private encryption and decryption key will act as a public key. Throughout this research paper, mathematical method that we use to generate public key and private key are matrix.